2014
DOI: 10.1016/j.rmed.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Dysnatremia, vasopressin, atrial natriuretic peptide and mortality in patients with community-acquired pneumonia

Abstract: HypoN is common at admission among CAP patients and is independently associated with mortality. HyperN is rare at admission among CAP patients but is also independently associated with mortality. The combination of sodium and CT-pro-AVP and MR-proANP levels achieved the highest prediction of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 35 publications
4
46
1
1
Order By: Relevance
“…ADM and AVP levels were also analyzed with the LMM method. Biological relevance of our results is supported by other studies, where similar changes in AVP and ADM levels were found in other diseases [36,37]. Moreover Castellano et al found that adrenomedullin gene induced more than 1.5-fold in C1-INH-HAE patients during attacks [38].…”
Section: Discussionsupporting
confidence: 90%
“…ADM and AVP levels were also analyzed with the LMM method. Biological relevance of our results is supported by other studies, where similar changes in AVP and ADM levels were found in other diseases [36,37]. Moreover Castellano et al found that adrenomedullin gene induced more than 1.5-fold in C1-INH-HAE patients during attacks [38].…”
Section: Discussionsupporting
confidence: 90%
“…Hyponatraemia occurs in 8%‐31% of adult patients with CAP with higher incidence in children (27%‐45%) and Legionella pneumonia(44%) . Hyponatraemia in CAP is usually mild (130‐134 mmol/L) and asymptomatic, yet epidemiological data consistently demonstrate increased mortality, more frequent ITU admission, and prolonged hospital stay, in patients with CAP and hyponatraemia. Consequently, hyponatraemia in CAP has been associated with an increase in hospital costs …”
Section: Introductionmentioning
confidence: 99%
“…A recent German study reported a high incidence of hyponatremia (31.8%) among patients with community-acquired pneumonia [6]. The degree of hyponatremia severity seemed to correlate with the patients' comorbidities (such as chronic heart failure, chronic renal disease, diabetes mellitus, and malignancies), higher severity of pneumonia, and higher inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of these comorbidities with sodium levels was weak and disappeared after inclusion in a multivariate model. The relationship of hyponatremia and higher pneumonia severity probably reflects the presence of hypovolemia, severe sepsis, and subsequent activation of vasopressin and natriuretic peptides secretion [6]. The decrease in the ability to reduce urine osmolality and excrete water loads and the increasing levels of ADH in the absence of antibiotic treatment [7] might be incriminated in pneumonia-induced hyponatremia.…”
Section: Discussionmentioning
confidence: 99%